ALTERNATIVE SELECTION OF DOMESTIC WASTEWATER MANAGEMENT SYSTEM ON SPECIFIC AREA WITH COST-BENEFIT ANALYSIS BASED ON SETTLEMENT TYPOLOGY (CASE STUDY: LOK BAINTAN AREA) - Iman Tauhid, Ahmad
Domestic wastewater from riverbanks is generally difficult to manage due to specific conditions on each typology of settlements in the area. Various kinds of settlement typologies emerge due to different types of houses, environmental conditions and socio-economic conditions of the people in an area, so modifications for wastewater management systems are required corresponding to each conditions of settlement typologies. This study aims to choose an alternative domestic wastewater management system that is suitable for each typology of settlements in the Lok Baintan area, Sungai Tabuk District. The analysis used to determine the settlement typologies is cluster analysis by K-Means non-hierarchical clustering. The alternative selection uses the cost-benefit analysis method which is by calculating the ratio of environmental and health benefits after the system is built to the investment and operational costs incurred during the study period (benefitcost ratio). Based on the results of cluster analysis, the Lok Baintan area can be divided into 3 typologies of settlements above the river (SS-1, SS-2, SS-3), 3 typologies of land settlements (DT-1, DT-2, DT-3), and 3 typologies of transitional settlements (TR-1, TR-2, TR-3). Type of house, population density, availability of clean water, type of private latrine, groundwater level, and availability of land are considered in the alternative formulation. The type of system and treatment technology with the highest BCR value for DT-1, DT-2, DT-3, TR-2, and TR-3 is on-site mixed system with modified concrete ring septic tank + upflow filter + wetland and flush toilet. The selected system and treatment technology for SS-1, SS- 2, SS-3, and TR-1 is on-site separated system with Tripikon-S + wetland and cemplung or flush toilet.